Enhancing Micro, Small, And Medium-Sized Businesses Efficiency with Financial Literacy - Ma'sumah, Siti; Hamidi, Luthfi; Puspitarini, Ida (International Journal of Social Science, Education, Communication and Economics, 2024)
Micro, small, and medium-sized businesses (MSMEs) play a big part in the economy, particularly in village economies. This is a result of the majority of rural firms still falling into the MSME category. Up until now, financial reports from MSMEs in rural areas have been infrequent. This is a result of MSME actors' ignorance regarding the preparation of financial reports. Low financial understanding translates into a low ability to produce financial reports. The MSME participants in Cilacap Regency's Sikanco Village, Nusawungu District, have not yet completed their financial reports for their companies. This is a result of their inexperience with financial report writing. Thus, it is impossible to accurately gauge the financial performance of MSMEs. As a result, help is required with both creating financial reports and raising awareness of financial literacy. This program helps with financial report preparation and raises awareness of financial literacy through the use of the Participatory Action Research (PAR) approach. MSME players came to the realization that financial report preparation is crucial to their firm after receiving support with it. Owners of MSME businesses become conscious of both their personal and company assets. As a result, helping to prepare MSME financial reports is crucial and beneficial for MSME participants. They make an effort to keep track of transactions and financial reports for their company, and the financial reports that have been generated are easily understandable. Residents developed an interest in and an understanding of the significance of financial reporting in order to mitigate the risk of business losses following their education. Additionally, MSME partners are growing increasingly interested in effectively managing family finances in order to improve their welfare since, through keeping track of household spending, they can identify areas where they can save more money and invest the proceeds.